Exploration of the social and economic impact of CSR programs in local communities: A Qualitative study - Samanlangi, Ilham; Rosalia, Olyvia; Firayani (Nomico, 2025)
Corporate Social Responsibility (CSR) programs play a crucial role in sustainable development, particularly in local communities affected by corporate operations. This study explores the social and economic impacts of PT Pertamina’s Reforestation and Greening Program as part of its CSR initiatives. Using a qualitative case study approach, this research collects data through in-depth interviews, field observations, and document analysis. The findings indicate that the program provides social benefits, including increased environmental awareness, active community participation in conservation efforts, and improved quality of life due to a greener environment. From an economic perspective, the program contributes to job creation, increased income through ecotourism and environmentally based businesses, and more sustainable local economic growth. However, challenges remain regarding funding sustainability, long-term community engagement, and risk mitigation of environmental degradation. Therefore, this study recommends a more sustainable CSR model, emphasizing collaboration between companies, the government, and local communities to ensure long-term benefits. These findings contribute to academic discussions and CSR practices, particularly in the context of environmental sustainability and economic empowerment of local communities.